Implementasi Program Pemeliharaan Jalan Di Dinas Pekerjaan Umum Dan Penataan Ruang (PUPR) Kabupaten Pandeglang - Rachmi Yulianti; Budi Hasanah (Program Studi Administrasi Negara Universitas Serang Raya, 2018)
This study aims to determine the Implementation of Road Maintenance Programs in the Public Works and Spatial Planning (PUPR) Service of Pandeglang District (Case Study in Pandeglang District). This research method is descriptive qualitative. Data collection techniques used are: Interview, observation, documentation. Research location of the Public Works and Spatial Planning (PUPR) Office of Pandeglang Regency and Pandeglang District. Based on the results of the study it can be concluded that: 1) Implementation of Road Maintenance programs in the Public Works and Spatial Planning (PUPR) Service of Pandeglang District (Pandeglang District Case Study) has been going well because the planned program has been realized in 2017 and adjusted to the given budget to the PUPR Service but not all maintenance can be carried out. 2) Supporting factors, namely the possibility of infrastructure funding that can be obtained not only from the APBD but the assistance from the Special Allocation Fund (DAK), the National Budget, assistance from the province and human resources and applicable regulations. The inhibiting factor of the implementation is of course the budget that is lacking but many roads must be handled so that it is not handled quickly, unexpected weather can slow down repairs